Peningkatan Kemampuan Representasi Matematis dan Keterampilan Sosial Siswa Melalui Pendekatan Pembelajaran Matematika Realistik - Yeni Listiana (Jurnal MathEducation Nusantara, 2018)
Abstract The research is quasi experiment. The population in this research were all of students’ in Junior High School at SMP Swasta Darul Ilmi Murni Deliserdang. Then randomly were selected two classes. Experiment class were given learning through Realistic Mathematics Education and control class were given conventional learning. The instrument are consisted of: mathematical representation ability test and social skills of the student questionnaire. Data was analyzed using two-way analysis of variance (ANOVA). Based on the analysis obtained some results, they are: (1) The increasing of mathematical representation’s ability who received lesson through Realistic Mathematics Education is higher than students’ who received conventional learning, (2) The increasing of students’ social skills who received lesson through Realistic Mathematics Education is higher than students who received conventional learning, (3) There is no interaction between learning approach and mathematical early ability to increase mathematical representation ability, (4) There is no interaction between learning approach and mathematical early ability to increase social skills of student. Descriptively also studied of the answers of the problem’s formulation, it was : students’ activity during learning using Realistic Mathematics Education was categorized as good. Keywords : Realistic Mathematics Education, Mathematical Representation Ability and Social Skills